Challenges and strategies in the inclusion of deaf students with limited access to Brazilian Sign Language (LIBRAS) in High School: An experience report from Pacajá (Research, Society and Development, 2026)
This study presents experience reports on the inclusion of deaf students in high school at a public school in Pacajá, with limited access to Brazilian Sign Language (LIBRAS). Therefore, this article aims to report the experience lived in a high school in the municipality of Pacajá, highlighting the main challenges and strategies adopted in the process of including deaf students with little access to LIBRAS. The research is qualitative, based on direct teaching experience, classroom observation, interviews with teachers, and document analysis. Over several years, eight deaf students were served, including one with intellectual disability associated with deafness and another with hearing impairment. It was observed that the students arrive at high school with incomplete literacy and significant impairment in text production, in addition to having basic to intermediate mastery of LIBRAS, requiring more advanced teaching to follow interpretations in class. It was also identified that deaf students prefer to interact with their peers, forming their own community within the school, instead of integrating with hearing students. Pedagogical strategies such as the use of visual resources, bilingual activities, LIBRAS seminars, and partnerships with universities have proven effective in promoting learning and inclusion. It is concluded that teacher training in LIBRAS, which refers to curricular adaptation and respect for the preferences of deaf students, is fundamental for effective school inclusion.6336